2020
DOI: 10.1016/j.childyouth.2020.105254
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of stress, anxiety and depression due to examination in Bangladeshi youths: A pilot study

Abstract: Highlights Factors of examination pressure of Bangladeshi tertiary level students are hardly researched. Stress, anxiety and depression was evaluated using DASS-21 for 210 youths aged between 17–25 years. The significant contributors are living with family, family time, sleeping pattern and diets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 40 publications
6
38
0
Order By: Relevance
“…The findings also indicate that students living without their families are experiencing more anxiety due to the stress of living alone and inadequate nutrient intake. This result is in line with the findings of Arusha & Biswas (2020) . The necessity of high-speed internet during this pandemic is immense, and it is compulsory for participating in e-learning.…”
Section: Discussionsupporting
confidence: 93%
“…The findings also indicate that students living without their families are experiencing more anxiety due to the stress of living alone and inadequate nutrient intake. This result is in line with the findings of Arusha & Biswas (2020) . The necessity of high-speed internet during this pandemic is immense, and it is compulsory for participating in e-learning.…”
Section: Discussionsupporting
confidence: 93%
“… 20 However, the authors of a study carried out among the youths of Bangladesh reported that living with family and spending time with parents reduce both anxiety and depression. 24 In our context, we think that the presence of another closed age member in the household may improve the sharing of life lessons, physical activity and thus lead to protection against depression.…”
Section: Discussionmentioning
confidence: 91%
“…If it is categorized as average age is 20,029 that includes in late adolescence. A balanced lifestyle with good socialization, will help late teens to reduce depression, anxiety and stress (Rayhan & Kishore, 2020). Late teens are particularly vulnerable with stress, heartache and anger being eliminated in ways that are unhealthy or even violent.…”
Section: Resultsmentioning
confidence: 99%